Less noise, more activation: multi band acquisition schemes for auditory fMRI - De Martino, Federico (Magn Reson Med, 2014)
PURPOSE: To improve acquisition in fMRI studies of audition by using multiband (MB) gradient-echo echo planar imaging (GE-EPI). METHODS: Data were acquired at 3T (Siemens Skyra) with a 32-channel head coil. Functional responses were obtained by presenting stimuli (tones and natural sounds [voices, speech, music, tools, animal cries]) in silent gaps between image acquisitions. Two-fold slice acceleration (MB2) was compared to a standard GE-EPI (MB1). Coverage and sampling rate (TR=3s) were kept constant across acquisition schemes. The longer gap in MB2 scans was used to present: 1) sounds of the same length as in conventional GE-EPI (type1; 800 ms stimuli); 2) sounds of double the length (type 2; 1600 ms stimuli). RESULTS: Functional responses to all sounds (i.e. main effect) were stronger when acquired with slice acceleration (i.e. shorter acquisition time). The difference between voice and non-voice responses was greater in MB2 type1 acquisitions (i.e. same length sounds as GE-EPI but presented in a longer silent gap) than in standard GEEPI acquisitions (interaction effect). CONCLUSION: Reducing the length of the scanner noise results in stronger functional responses. Longer “silent” periods (i.e. keeping the sound length the same as in standard acquisitions) result in stronger response to voice compared to non-voice stimuli.